Tradisi Nginang Pada Masyarakat Suku Jawa Desa Gondang Rejo, Pekalongan - Arum Ramadhani, Sekar; Karsiwan (Universitas Cenderawasih, 2024)
The tradition of Nginang or betel is a typical cultural practice among Javanese people, especially in Gondang Rejo Village, Pekalongan. This tradition is carried out by chewing betel, whiting (enjet), tobacco (mbako), and gambier in a social procession involving various cultural elements. This research aims to explain the tradition or habit of nginang among the Javanese people in a village called Gondang Rejo, Pekalongan sub-district, Kab. East Lampung. This research uses a qualitative descriptive approach method. Through observation, interviews and documentation analysis for data collection. The research results show that the Nginang Tradition is a practice that is highly respected by the Javanese people in Gondang Rejo Village. People believe that the nginang tradition can care for and maintain healthy teeth, the people who still have a lot of nginang are women. The Nginang tradition is a typical cultural practice among Javanese people, especially in Gondang Rejo Village, Pekalongan. Apart from that, the Nginang Tradition also has an important role in maintaining the cultural identity of the Javanese people and strengthening relations between community members.